Neurodegeneration with Trichorrhexis Invaginata - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Two siblings are reported from the Medical College of Ohio with an autosomal recessive syndrome characterized by hair and skin abnormalities, hypoplastic nails, hypotonia, areflexia, and progressive neurological deterioration.